2000
DOI: 10.4049/jimmunol.164.10.5055
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Engagement on Synovial Fibroblast Up-Regulates Production of Vascular Endothelial Growth Factor

Abstract: We tested the impact of CD40 engagement on the production of vascular endothelial growth factor (VEGF) from rheumatoid synovial fibroblasts. Fibroblast-like synovial cells (FLS) were prepared from the synovial tissues of rheumatoid arthritis patients and cultured in the presence of CD40 ligand-transfected (CD40L+) L cells. VEGF levels were determined in the culture supernatants by ELISA. Stimulation of FLS by CD40L+ L cells increased the production of VEGF by 4.1-fold over the constitutive levels of unstimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 45 publications
5
81
1
2
Order By: Relevance
“…Autoradiographs are representative of 6 independent experiments. promote activation responses including the expression of the angiogenesis factor VEGF (12,41,53,62). In this study, we identified a CD40-responsive element for VEGF expression in EC and we show that it resides within a 68-bp region of the VEGF promoter.…”
Section: Discussionmentioning
confidence: 87%
“…Autoradiographs are representative of 6 independent experiments. promote activation responses including the expression of the angiogenesis factor VEGF (12,41,53,62). In this study, we identified a CD40-responsive element for VEGF expression in EC and we show that it resides within a 68-bp region of the VEGF promoter.…”
Section: Discussionmentioning
confidence: 87%
“…Other investigators have also demonstrated that CD68ϩ synovial macrophage lineage cells as well as fibroblast-like synoviocytes (FLS) express CD40 (8,9). The ligation of CD40 augments the production of IL-12 in synovial cells and synovial fluid macrophages from RA patients (10,11) and enhances the expression of CD54, CD106, IL-6 (12), stromal cell-derived factor 1 (13), and vascular endothelial cell growth factor (14). In vivo, treatment with a monoclonal antibody (mAb) against CD154 prevents the development of type II collagen-induced arthritis in mice (15).…”
mentioning
confidence: 99%
“…17 Stimulation of CD40 on endothelial cells, monocytes, fibroblasts and multiple myeloma cells upregulates production of VEGF by these cells. [18][19][20] Furthermore, neutralisation of autocrine VEGF by anti-VEGF antibody (Ab) completely abolished the mitogenic effect of CD154 on endothelial cells. 18 In CLL cells, ligation of CD40 by CD154 is known to inhibit spontaneous and drug-induced cell death.…”
Section: Introductionmentioning
confidence: 99%